Полоса везения: Роман / В. А. Демьянова - Демьянова Валентина Алексеевна (Детектив глазами женщины, 2002)
Экземпляры: Ф. 9 (20200320) / Инвентарный номер: 40877 / Цена: 22.50 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Д 32 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44